Detection of pup odors by non-canonical adult vomeronasal neurons expressing an odorant receptor gene is influenced by sex and parenting status. Issue 1 (December 2016) - Nakahara, Thiago; Cardozo, Leonardo; Ibarra-Soria, Ximena; Bard, Andrew; Carvalho, Vinicius; Trintinalia, Guilherme; Logan, Darren; Papes, Fabio
Abstract Background Olfaction is a fundamental sense through which most animals perceive the external world. The olfactory system detects odors via specialized sensory organs such as the main olfactory epithelium and the vomeronasal organ. Sensory neurons in these organs use G-protein coupled receptors to detect chemosensory stimuli. The odorant receptor (OR) family is expressed in sensory neurons of the main olfactory epithelium, while the adult vomeronasal organ is thought to express other types of receptors. Results Here, we describeOlfr692, a member of theOR gene family identified by next-generation RNA sequencing, which is highly upregulated and non-canonically expressed in the vomeronasal organ. We show that neurons expressing this gene are activated by odors emanating from pups. Surprisingly, activity inOlfr692 -positive cells is sexually dimorphic, being very low in females. Our results also show that juvenile odors activate a large number ofOlfr692 vomeronasal neurons in virgin males, which is correlated with the display of infanticide behavior. . In contrast, activity substantially decreases in parenting males (fathers), where infanticidal aggressive behavior is not frequently observed. Conclusions Our results describe, for the first time, a sensory neural population with a specific molecular identity involved in the detection of pup odors. Moreover, it is one of the first reports of a group of sensory neurons the activity of which is sexually dimorphic and depends on social status. Our data suggest that theOlfr692 population is involved in mediating pup-oriented behaviors in mice.